Surgery and postoperative radiotherapy affect the prognosis of esophageal cancer: A SEER analysis. Issue 9 (3rd March 2023) - Yang, Wenwen; Yang, Yanjiang; Ma, Xiang; Ma, Minjie; Han, Biao
Abstract : The principal treatment modalities for esophageal cancer are radiation, chemotherapy and surgery or a combination of them. In some sense, technological advances have tremendously heightened patients' survival rates. Nevertheless, the debate on the prognostic value of postoperative radiotherapy (PORT) has never ceased. On that account, this study made an effort to probe deep into the effects of PORT and surgery on the prognosis of stage III esophageal cancer. Our study included patients diagnosed with stage III esophageal cancer between 2004 and 2015 through the Surveillance, Epidemiology, and End Results (SEER) program. We performed propensity score matching (PSM) on the basis of whether surgery was carried out and whether PORT conducted. We identified the independent risk factors by multivariate Cox regression and constructed a nomogram model. In this research, we included 3940 patients, and the median follow-up is 14 months: 1932 cases without surgery; 2008 cases with surgery, and 322 cases of them underwent PORT. In the postPSM patient cohort, patients who underwent surgery had a median overall survival rate (OS) of 19.0 (95% confidence interval [CI] 17.2–20.8) and a median cancer-specific survival rate (CSS) of 23.0 (95% CI 20.6–25.3) months, which were remarkably higher than those without surgery ( P < .001). The OS（ P < .05）and CSS（ P < .05）of the patients who underwent PORT were lower than those who did not. Similar results were obtained in the groups of N0 and N1. This study revealed surgery can heighten patients' survival rate, while PORT could not elevate patients' survival rate in stage III esophageal cancer patients.